2009
DOI: 10.1038/nature08065
|View full text |Cite
|
Sign up to set email alerts
|

Hexameric assembly of the proteasomal ATPases is templated through their C termini

Abstract: Substrates of the proteasome are recognized and unfolded by the regulatory particle (RP), then translocated into the core particle (CP) to be degraded1. A hetero-hexameric ATPase ring, containing subunits Rpt1-Rpt6, is situated within the base subassembly of the RP1. The ATPase ring sits atop the CP, with the Rpt C-termini inserted into pockets in the CP2–6. We have identified a novel function of the Rpt proteins in proteasome biogenesis through deleting the C-terminal residue from each Rpt. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
283
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(303 citation statements)
references
References 31 publications
18
283
2
Order By: Relevance
“…6c, right panel), suggesting that almost all proteasomes contained stoichiometric amounts of the fusion proteins. These observations support the CP template assembly model of the RP 39 . Furthermore, structural analysis by cryo-electron microscopy revealed that the Pre6-Rpt2-fused proteasome was almost indistinguishable from the wild-type proteasome (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…6c, right panel), suggesting that almost all proteasomes contained stoichiometric amounts of the fusion proteins. These observations support the CP template assembly model of the RP 39 . Furthermore, structural analysis by cryo-electron microscopy revealed that the Pre6-Rpt2-fused proteasome was almost indistinguishable from the wild-type proteasome (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Our FCS analysis did not detect proteasome assembly intermediates in wild-type cells, probably because such intermediates are not abundant [37][38][39][40] . Previous studies using a specific importin-a mutant, srp1-49, suggested that nucleocytoplasmic transport mediated by importin a/b is coupled to proteasome biogenesis [19][20][21]23 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Two competing models exist for RP assembly ( Funakoshi et al , 2009; Le Tallec et al , 2009; Park et al , 2009; Roelofs et al , 2009). The first posits that RP assembly occurs in modules independent of the CP with the help of four RP-dedicated chaperones, named Hsm3, Nas2, Nas6 and Rpn14 ( Funakoshi et al , 2009).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…The first posits that RP assembly occurs in modules independent of the CP with the help of four RP-dedicated chaperones, named Hsm3, Nas2, Nas6 and Rpn14 ( Funakoshi et al , 2009). In contrast, the second model proposes that the CP serves as a scaffold for the heterohexameric ATPase ring of the RP base ( Park et al , 2009). The second model, however, appears less likely with regard to X-ray structure analysis showing that the RP-dedicated chaperones hinder the association between the RP base and CP α ring ( Barrault et al , 2012).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%